2010
DOI: 10.1261/rna.2483611
|View full text |Cite
|
Sign up to set email alerts
|

Ku can contribute to telomere lengthening in yeast at multiple positions in the telomerase RNP

Abstract: Unlike ribonucleoprotein complexes that have a highly ordered overall architecture, such as the ribosome, yeast telomerase appears to be much more loosely constrained. Here, we investigate the importance of positioning of the Ku subunit within the 1157-nt yeast telomerase RNA (TLC1). Deletion of the 48-nt Ku-binding hairpin in TLC1 RNA (tlc1D48) reduces telomere length, survival of cells with gross chromosomal rearrangements, and de novo telomere addition at a broken chromosome end. To test the function of Ku … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(88 citation statements)
references
References 54 publications
7
80
1
Order By: Relevance
“…The strongest evidence supporting this hypothesis is provided by experiments showing that large parts of the RNA can be moved to different positions in the RNA without loss of telomerase function (Zappulla and Cech 2004;Zappulla et al 2011). The overall idea then was that Protein-RNA interactions were required for overall tethering but that the final organization of the RNP could be heterogeneous and achieved in various ways (Zappulla and Cech 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest evidence supporting this hypothesis is provided by experiments showing that large parts of the RNA can be moved to different positions in the RNA without loss of telomerase function (Zappulla and Cech 2004;Zappulla et al 2011). The overall idea then was that Protein-RNA interactions were required for overall tethering but that the final organization of the RNP could be heterogeneous and achieved in various ways (Zappulla and Cech 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the budding yeast telomerase RNA does allow permutations of certain parts of the RNA. For example, the yKu-binding stem-loop as well as the complete stem III/stem IV arm domain can be moved to other locations in the RNA without complete loss of functionality (Zappulla and Cech 2004;Zappulla et al 2011). …”
mentioning
confidence: 99%
“…These experiments call into question the hypothesis that Ku serves as a simple bridging factor to recruit telomerase. Nonetheless, the insertion of an additional KBS into the TLC1 RNA results in a telomere hyperelongation phenotype, indicating that the Ku-TLC1 interaction may contribute to telomere homeostasis in capacities beyond nuclear localization (Zappulla et al 2011). For example, the Ku-TLC1 interaction is also thought to contribute to anchoring of the telomerase to the nuclear envelope (Schober et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ku and Sm 7 are important, but not essential, for telomerase function. Loss of Ku binding to TLC1 results in shortened telomeres (Peterson et al 2001;Bertuch and Lundblad 2003;Stellwagen et al 2003) (in addition to a 50% drop in TLC1 abundance [Zappulla et al 2011]), and Ku has been reported to bind telomeres (Gravel et al 1998). These findings, as well as other studies, have suggested that Ku helps to recruit telomerase to telomeres in yeast by sequentially binding DNA and TLC1 RNA (Stellwagen et al 2003;Pfingsten et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these nucleotides in the arms have been shown to be dispensable for basal telomerase activity; a miniature TLC1 (Mini-T) with 657 nt deleted from the arms is functional in vitro and is able to maintain short but functional telomeres in vivo (Zappulla et al 2005). Furthermore, the Est1 and Ku accessory subunit-binding sites on the arms of TLC1 can be repositioned on the RNA and still function (Zappulla and Cech 2004;Zappulla et al 2011).…”
Section: Introductionmentioning
confidence: 99%